Plan estratégico del Colegio Fiscal Técnico Monserrate Álava de González - González Solórzano, Rosangela Del Jesús (2012)
This paper presents a proposed strategic plan, which designed aseries of rules, designed to meet the demands of the environment and place the institution in an advantageous relationship for the future. To carry out the structuring of this, we applied an interview which was determined by the current situation of the school, the same that it had no planning, putting at a disadvantage due to the need of wanting to be one of the institutions that contribute to educational development relating to this environment. For this reason we conducted a strategic plan for the school fiscal Álava technical Monserrate Gonzalez the same consisting of goals and objectives to achieve the long term. To raise awareness of this research was achieved strategic planto socialize the entire faculty and staff of the institution, whichissued the mission, vision, objectives, policies, values, philosophy and strategies, demonstrating the willingness and interest by them to bring to reality its implementation, oncespecified strategies must change in operations defined as programs and projects. The methodology used in this study wasthe statistical method which helped meet the target proposed bythe authors. At the end result was obtained as a strategic planning that focuses and directs social change by encouraging astep forward for the educational institution and community.